Primary type specimens of sucking lice (Insecta: Phthiraptera: Anoplura) in the U.S. National Museum of Natural History, Smithsonian Institution - Durden, Lance A.; Adams, Nancy E. (Zootaxa, 2005)
An annotated list is presented of the 110 primary types (holotypes, lectotypes, syntypes, or neotypes) of sucking lice (Insecta: Phthiraptera: Anoplura) deposited in the U.S. National Museum of Natural History (USNM), Smithsonian Institution, as of May 2005. Annotations for each taxon are listed alphabetically by specific epithet, and are followed by the original generic assignment and (in parentheses) the current family designation. Next, the author, year of description, and original citation are provided. The primary type held in the USNM (with USNM type number, slide number and other relevant data, if these were assigned), original collection data, current taxonomic assignment (if different from the original designation), and additional taxonomic remarks, if relevant, are then given. Brief information on allotypes and paratypes are included if these are mounted on the same microscope slide as the primary type or if they are otherwise relevant. The types include those of the type species of seven genera (Abrocomaphthirus Durden & Webb, Atopophthirus Kim & Emerson, Haematopinoides Osborn, Latagophthirus Kim & Emerson, Pecaroecus Babcock &Ewing, Phthirpediculus Ewing, and Sathrax Johnson) one of which is the type genus of a family (Pecaroecidae). Primary types for five species of Anoplura that have not yet been described, and for another four species that were described in an unpublished dissertation are also deposited in the USNM. Hosts and collection data for these nine specimens are briefly mentioned after the main list; however, species names are excluded because these names currently have no nomenclatural standing. A neotype specimen is designated for Haematopinus montanus Osborn, 1896, a taxon which is currently treated as a junior synonym of Linognathoides laeviusculus (Grube, 1851).